The costs and benefits of compassion for Ottawa's frontline shelter workers - MacDonald, Ann (University of Ottawa (Canada), 2009)
The purpose of this preliminary study is to assess levels of compassion fatigue, burnout, and compassion satisfaction in frontline shelter workers, with consideration of demographic and spiritual characteristics as possible ameliorating factors. The study participants are frontline workers in three emergency men's shelters in Ottawa. Research in related fields, particularly health care and mental health, indicates a prevalence of compassion fatigue and burnout among human service personnel, either as a result of direct exposure to acts of aggression (primary exposure) or as a result of working with persons in distress (secondary exposure). The Professional Quality Of Life Scale was used to assess the responses of frontline shelter workers on measures of compassion fatigue, burnout, and compassion satisfaction. The Spiritual Well-Being and Community Spirituality Scales were used to assess spirituality on the domains of faith, hope and love.
Keywords: Philosophy.